2006
DOI: 10.1093/humrep/del306
|View full text |Cite
|
Sign up to set email alerts
|

Is the PCOS diagnosis solved by ESHRE/ASRM 2003 consensus or could it include ultrasound examination of the ovarian stroma?

Abstract: In the grey area between NIH and ESHRE/ASRM classifications, UCSC criteria could identify a subgroup of women, missed by NIH criteria, with more pronounced stigmas than those identified by ESHRE/ASRM criteria alone, and who may profit more from a targeted therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 33 publications
5
47
3
1
Order By: Relevance
“…Preadipocytes are known to have androgen receptors and high androgen levels have been shown to induce selective IR in cultured adipocytes (Belosi et al, 2006). Also, long term androgen administration in female-to-male transsexuals has been shown to induce the development of abdominal obesity and IR (Elbers et al, 2003).…”
Section: Pcos and Obesitymentioning
confidence: 99%
“…Preadipocytes are known to have androgen receptors and high androgen levels have been shown to induce selective IR in cultured adipocytes (Belosi et al, 2006). Also, long term androgen administration in female-to-male transsexuals has been shown to induce the development of abdominal obesity and IR (Elbers et al, 2003).…”
Section: Pcos and Obesitymentioning
confidence: 99%
“…27 However, in research settings, subdividing PCOS into more discrete categories is imperative if we are to clearly define incidence, degree of symptomology and health risks among all variants of PCOS (Table 3). [28][29][30][31][32] In the most comprehensive study aimed at evaluating the phenotypic spectrum of PCOS, DiamantiKandarakis et al showed hyperandrogenic and anovulatory phenotypes of PCOS to be the most insulin resistant-irrespective of BMI or central adiposity. 33 Their approach to elucidating differences among PCOS phenotypes involved a number of physicians and ultrasonographers working cooperatively to diagnose and evaluate a large study population.…”
Section: Elucidating the Phenotypic Spectrum Of Polycystic Ovary Syndmentioning
confidence: 99%
“…However, Asian women with PCOS are less likely to have metabolic dysfunction, IR, and obesity compared with Caucasian women with PCOS (15)(16)(17). There is little data on omentin levels within the context of PCOS (18,19).…”
Section: Introductionmentioning
confidence: 99%